Comparison of two cooling protocols for llama semen: with and without collagenase and seminal plasma in the medium. (25th August 2016) - Carretero, M. I.; Giuliano, S. M.; Arraztoa, C. C.; Santa Cruz, R. C.; Fumuso, F. G.; Neild, D. M.
Summary: Seminal plasma (SP) of South American Camelids could interfere with the interaction of spermatozoa with the extenders; therefore it becomes necessary to improve semen management using enzymatic treatment. Our objective was to compare two cooling protocols for llama semen. Twelve ejaculates were incubated in 0.1% collagenase and then were divided into two aliquots. One was extended in lactose and egg yolk (LEY) (Protocol A: collagenase and SP present). The other aliquot was centrifuged, and the pellet was resuspended in LEY (Protocol B: collagenase and SP absent). Both samples were maintained at 5°C during 24 hr. Routine and DNA evaluations were carried out in raw and cooled semen. Both cooling protocols maintained sperm viability, membrane function and DNA fragmentation, with Protocol A showing a significantly lowered total and progressive motility ( p  < .05) and Protocol B showing a significant increase in chromatin decondensation ( p  < .05). Protocol A avoids centrifugation, reducing processing times and making application in the field simpler. However, as neither protocol showed a significant superiority over the other, studies should be carried out in vivo to evaluate the effect on pregnancy rates of the presence of collagenase and SP in semen samples prior to either cooling or freeze‐thawing.